Removal of nickel by using microflora in drain - Norasiha, Hamid (2008)
The aims of this work was to study the influence of influent chemical oxygen demand (COD), the removal of initial concentration and the growth of biomass, effects from removal of nickel in wastewater by using microflora in drain. This experiment was using sequencing batch reactor (SBR) system with organic loading rate which range between 0.40mg.L.day to 4.00mg/L.day. The efficiency of COD reduction was found to be 51.5% at organic loading rate 1.54mg/l.day. 35.6% of nickel removal due to biodegradation was achieved at 4.00mg/l.day of organic loading rate. The growth of biomass was increased 310mg/l at 0.40mg/l.day organic loading rate. It is concluded that SBR system can effectively be used in the treatment of nickel wastewater for removal of ions nickel and reduction of COD.